2012
DOI: 10.1017/s0007114512004680
|View full text |Cite
|
Sign up to set email alerts
|

Improving the growth performance and cholesterol metabolism of rainbow trout (Oncorhynchus mykiss) fed soyabean meal-based diets using dietary cholesterol supplementation

Abstract: A 9-week feeding trial was conducted to evaluate the effects of dietary cholesterol supplementation at different levels (0, 0·3, 0·6, 0·9, 1·2 and 1·5 %) on growth and cholesterol metabolism of rainbow trout (Oncorhynchus mykiss) fed soyabean meal (SBM)-based diets. Daily growth coefficient (DGC) steadily increased when the supplemental cholesterol was increased by up to 1·2 %, but declined upon further addition. The total cholesterol (TC), HDL-cholesterol (HDL-C) and LDL-cholesterol (LDL-C) levels in plasma g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
41
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 68 publications
8
41
3
Order By: Relevance
“…HDL carries cholesterol from the peripheral tissues to the liver, whereas LDL carries cholesterol from the liver to the peripheral tissues. Thus, the LDL-C, HDL-C ratio can be used as a sign of cholesterol transport [60]. In our study, the dietary A-OKGM supplementation significantly enhanced the serum LDL-C, HDL-C ratio in fish fed with 0.4% and 1.6% A-OKGM diets.…”
Section: Discussionsupporting
confidence: 57%
“…HDL carries cholesterol from the peripheral tissues to the liver, whereas LDL carries cholesterol from the liver to the peripheral tissues. Thus, the LDL-C, HDL-C ratio can be used as a sign of cholesterol transport [60]. In our study, the dietary A-OKGM supplementation significantly enhanced the serum LDL-C, HDL-C ratio in fish fed with 0.4% and 1.6% A-OKGM diets.…”
Section: Discussionsupporting
confidence: 57%
“…However, in the present study, juvenile rainbow trout fed for 12 weeks with either diet showed no differences in any of the measured growth and feed efficiency parameters. In a recent study on the same species [26], but using diets containing fish oil and primarily focusing on the issue of soybean inclusion in aquafeed and its hypocholesterolemic effect [40], a positive effect of dietary cholesterol supplementation on fish performances was observed. Similarly, mixed results are currently available for other teleost species.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the availability of dietary cholesterol has been shown to affect the fatty acid metabolism [15][18], however, there have been only a few studies investigating dietary supplementation of cholesterol in fish feed [19][26]. These were all implemented using diets containing abundant levels of fish oil, and thus even the non-fortified (control) treatments were providing large amounts of dietary cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon may be associated with a deficiency of cholesterol (Deng et al, ; Hossain, Focken, & Becker, ) or some anti‐nutritional factors such as saponin (Messina, ), phytosterol (Madani, Frenoux, Prost, & Belleville, ) or non‐starch polysaccharides (Deng et al, ) in SBM. In addition, studies found that cholesterol supplementation in the diet can enhance the growth performance and feed intake of channel catfish (Twibell & Wilson, ), rainbow trout (Deng, Bi, et al, ) and turbot (Yun et al, ; Yun, Mai, & Zhang, ) when the fish were fed high‐SBM diets. However, a report for Atlantic salmon found that dietary cholesterol showed no effects on growth, mortality and nutrient digestibility (Bjerkeng, Storebakken, & Wathne, ).…”
Section: Introductionmentioning
confidence: 99%